Maintaining Maternal and Child Health Services During the Ebola Outbreak: Experience from Pujehun, Sierra Leone - Quaglio, GianLuca (PLoS Curr, 2016)
BACKGROUND: During the Ebola outbreak the overall confidence of the population in the national health system declined in Sierra Leone, with a reduction in the use of health services. The objective of this study is to provide information on understanding of how Ebola impacted maternal and child health services in Sierra Leone. Data come from an operational setting which is representative of the communities affected by the outbreak. METHODS: By integrating hospital registers and contact tracing form data with healthcare workers and local population interviews, the transmission chain was reconstructed. Data on the utilization of maternal and neonatal health services were collected from the local district’s Health Management Information System. The main measures put in place to control the Ebola epidemic were: the organization of a rapid response to the crisis by the local health authorities; triage, contact tracing and quarantine; isolation, clinical management and safe burials; training and community sensitization. RESULTS: A total of 49 case patients were registered between July and November 2014 in the Pujehun district. Hospitalization rate was 89%. Overall, 74.3% of transmission events occurred between members of the same family, 17.9% in the community and 7.7% in hospital. The mean number of contacts investigated per case raised from 11.5 in July to 25 in September 2014. The 2014 admission trend in the pediatric ward shows a decrease after beginning of June: the reduction was almost significant in the period July-December (p 0.05). The admission in the maternity ward showed no statistical differences in comparison with the previous year (p 0.07). Also the number of deliveries appeared to be similar to the previous year, without significant variations (p 0.41). CONCLUSION: The Ebola outbreak reduced the number of patients at hospital level in Pujehun district. However, the activities undertaken to manage Ebola, reduced the spread of infection and the impact of the disease in mothers and children. A number of reasons which may explain these results are presented and discussed.